2021
DOI: 10.1186/s40478-021-01245-z
|View full text |Cite
|
Sign up to set email alerts
|

Importance of extracellular vesicle secretion at the blood–cerebrospinal fluid interface in the pathogenesis of Alzheimer’s disease

Abstract: Increasing evidence indicates that extracellular vesicles (EVs) play an important role in the pathogenesis of Alzheimer’s disease (AD). We previously reported that the blood–cerebrospinal fluid (CSF) interface, formed by the choroid plexus epithelial (CPE) cells, releases an increased amount of EVs into the CSF in response to peripheral inflammation. Here, we studied the importance of CP-mediated EV release in AD pathogenesis. We observed increased EV levels in the CSF of young transgenic APP/PS1 mice which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 115 publications
(132 reference statements)
1
35
0
Order By: Relevance
“…In agreement with this, both TNFR1 deficiency and treatment with a TNFR1 inhibitor prevented the Aβ-induced cognitive decline ( 196 ). Additionally, also treatment with an inhibitor of EV production had the same effect ( 195 ). Based on these results, it is tempting to speculate that the combined effect of systemic inflammation and the presence of Aβ might further worsen AD disease progression among others via specific mechanisms at the blood-CSF barriers, such as loss of barrier integrity and EV release, which on their turn further aggravate neuroinflammation.…”
Section: Systemic Inflammation Affects Different Characteristics Of Ad Pathologymentioning
confidence: 94%
See 1 more Smart Citation
“…In agreement with this, both TNFR1 deficiency and treatment with a TNFR1 inhibitor prevented the Aβ-induced cognitive decline ( 196 ). Additionally, also treatment with an inhibitor of EV production had the same effect ( 195 ). Based on these results, it is tempting to speculate that the combined effect of systemic inflammation and the presence of Aβ might further worsen AD disease progression among others via specific mechanisms at the blood-CSF barriers, such as loss of barrier integrity and EV release, which on their turn further aggravate neuroinflammation.…”
Section: Systemic Inflammation Affects Different Characteristics Of Ad Pathologymentioning
confidence: 94%
“…As mentioned above, systemic inflammation not only has an impact on the integrity of the BBB, but LPS-induced systemic inflammation in mice also disrupts the blood-CSF barrier ( 47 , 177 ) and induces the release of extracellular vesicles (EVs) ( 32 ); both resulting in increased neuroinflammation. Interestingly, also Aβ on its own has a direct impact on the blood-CSF barrier: induction of morphological changes of the CPE cells, decreased expression of TJ components, loss of barrier integrity, and EV release into the CSF ( 47 , 194 , 195 ). Analysis of human gene expression data comparing control and AD patient choroid plexus tissue revealed that TNF/TNFR1 signaling was upregulated in AD suggesting an involvement of this pathway in the blood-CSF barrier associated changes in AD ( 196 ).…”
Section: Systemic Inflammation Affects Different Characteristics Of Ad Pathologymentioning
confidence: 99%
“…To address this, we prepared choroid plexus explants from NPC1 −/− and NPC1 +/+ mice of 9 weeks and purified EVs from the choroid plexus explant supernatant via size exclusion chromatography (Figure 5A). The quality of the EV fractions were verified as we reported before (Vandendriessche et al, 2021) and according to the MISEV18 guidelines (Thery et al, 2018). Next, purified EVs were transferred to mixed cortical cultures (MCCs) of NPC1 +/+ mice and 24 h later, both MCC cells and cell supernatant were analyzed.…”
Section: Extracellular Vesicles In Cerebrospinalmentioning
confidence: 99%
“…Choroid plexus explants were prepared as we described previously (Balusu et al, 2016b;Vandendriessche et al, 2021). In short, 9 weeks old NPC1 +/+ and NPC1 −/− mice were anesthetized and transcardially perfused with serum free DMEM-F12 medium (11320074; Gibco) after which the choroid plexus (CP) tissue was dissected.…”
Section: Choroid Plexus Explantsmentioning
confidence: 99%
“…The strong endocytic activity at the blood–CSF barrier is probably related to the extensive metabolic and synthetic functions of the CP [ 36 ]. Moreover, our research group identified the implication of CP derived EVs in blood to brain communication [ 38 ] and the importance of CP-mediated EV release in AD pathogenesis [ 39 ]. Furthermore, also signaling of CP derived EVs to neuronal stem cells (NSCs) in the brain neurogenic niche via miR-204 was reported [ 40 ].…”
Section: Barriers In Brain Drug Deliverymentioning
confidence: 99%